Exploring the anti-erosive potential of film-forming polymers and fluoride on salivary pellicle modification - Sakae, Letícia Oba; Niemeyer, Samira Helena; Borges, Alessandra Bühler [UNESP]; Scaramucci, Taís; Carvalho, Thiago Saads (Springer Nature, 2025)
ObjectivesTo investigate the effect of solutions containing film-forming polymers on salivary pellicle modification for protection against dental erosion.Materials and methodsThree polymers were tested: Chitosan, Carbopol, and Linear sodium polyphosphate (LPP), each with or without sodium fluoride (F). Control groups were deionized water, F only, and tin/fluoride (Sn/F, positive control). Bovine enamel specimens underwent 10 cycles consisting of: 1 min salivary pellicle formation, 1 min modification with experimental solutions (n = 15/solution), 28 min salivary pellicle formation, and an erosive challenge (1 min for the first 5 cycles, 5 min for the last 5 cycles, totaling 30 min). Relative surface hardness (rSH), surface loss (SL), and calcium release (CaR) were analyzed after 5 and 30 min of erosion. The wettability of enamel in the presence and absence of the pellicle promoted by the solutions was also evaluated.ResultsChitosan showed a protective effect, with best results in rSH after 30 min in the no F subgroup, and when combined with F, it had similar performance to Sn/F. Carbopol showed the least protection, with the greatest loss of rSH and highest CaR, while LPP performed similarly to Carbopol whether combined or not to F. All polymer solutions exhibited higher wettability in the presence of the pellicle.ConclusionsOnly Chitosan modified the pellicle and improved its protective effect against erosion. The pellicle may hinder the adsorption of negatively charged polymers, reducing their protective potential.Clinical RelevanceChitosan may be a promissing agent for incorporation into erosion-preventive oral care products.